Kinematics modeling of redundant manipulator based on screw theory and Newton-Raphson method. Issue 1 (1st April 2022) - Ge, Dawei
Abstract: In this paper, forward kinematics and inverse kinematicsis algorithms are proposed to solve the problem that the redundant manipulator has more freedom than the traditional manipulator and cannot directly solve the inverse kinematics analytical solution. Firstly, the forward kinematics model is established through the screw theory; secondly, Newton-Raphson method is used to solve the inverse kinematics of the manipulator. Finally, the algorithms of redundant manipulator are verified through an example simulated by Matlab Robotics toolbox. The results show that the kinematic algorithms are correct, which provides a good algorithm basis for subsequent dynamic control.